Trends in Special Medicare Payments and Service Utilization for Rural Areas in the 1990s - Farley, Donna O. (RAND Corporation, 2002)
This report analyzes special payments that Medicare has been making to rural providers. These special payments are intended to support the rural health care infrastructure to help ensure access to care for Medicare beneficiaries. The research provides a comprehensive overview of these payments, including documentation of the supply of providers, trends in payments, and Medicare costs per beneficiary. Four types of special payments were examined: (1) payments to sole community hospitals, Medicare-dependent hospitals, and rural referral centers; (2) reimbursements to rural health clinics and federally qualified health centers; (3) bonus payments to physicians in rural health professional shortage areas; and (4) capitation payments in rural counties.